2019
DOI: 10.1080/14767058.2019.1572740
|View full text |Cite
|
Sign up to set email alerts
|

Medical indications for primary cesarean delivery in women with and without disabilities

Abstract: Background: Prior research has found that women with disabilities are more likely to deliver by cesarean than are women without disabilities. It is not clear whether all of the cesarean deliveries among women with disabilities are medically necessary.Objectives: To examine the associations between maternal disability status and type, mode of delivery, and medical indications for cesarean delivery in California deliveries. Study design:Retrospective cohort study of all nulliparous births in California between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…67,80,81 Findings from a recent populationbased study comparing medical indications for cesarean delivery among women with and without disabilities in California indeed suggests that disability itself may be treated as an indication for cesarean delivery in many cases. 82 Specifically, the authors found that women with disabilities who had prelabor scheduled cesarean deliveries had significantly lower odds of having a medical indication for cesarean delivery, compared with women without disabilities. 82 These individual, provider, and system-level factors should be investigated further to understand reasons for perinatal complications in women with disabilities.…”
Section: Systematic Reviewsmentioning
confidence: 98%
See 1 more Smart Citation
“…67,80,81 Findings from a recent populationbased study comparing medical indications for cesarean delivery among women with and without disabilities in California indeed suggests that disability itself may be treated as an indication for cesarean delivery in many cases. 82 Specifically, the authors found that women with disabilities who had prelabor scheduled cesarean deliveries had significantly lower odds of having a medical indication for cesarean delivery, compared with women without disabilities. 82 These individual, provider, and system-level factors should be investigated further to understand reasons for perinatal complications in women with disabilities.…”
Section: Systematic Reviewsmentioning
confidence: 98%
“…82 Specifically, the authors found that women with disabilities who had prelabor scheduled cesarean deliveries had significantly lower odds of having a medical indication for cesarean delivery, compared with women without disabilities. 82 These individual, provider, and system-level factors should be investigated further to understand reasons for perinatal complications in women with disabilities.…”
Section: Systematic Reviewsmentioning
confidence: 98%
“…The regression model examining initiation of prenatal care calculated the RR of women in each disability group (compared with those without disabilities) delaying care until the second or third trimester instead of initiating care in the first trimester (reference level). In the regression models of number of prenatal visits, the typically recommended number of visits (11)(12)(13)(14) was the reference level. Two analyses were conducted to calculate the RR of women with disabilities having: (1) fewer visits than recommended (zero to ten vs [11][12][13][14] and (2) more than the typically recommended number of visits (≥15 vs [11][12][13][14].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Women with disabilities are also substantially more likely to deliver by cesarean, with the medical necessity of cesarean delivery not always clear. 3,4,[10][11][12][13][14] In addition, women with disabilities are more likely to experience pregnancy complications, such as gestational diabetes and preeclampsia. 2,5,[8][9][10][11]13 The reasons for these adverse outcomes among women with disabilities are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Research to date has demonstrated disparities for women with disabilities in prenatal care utilization and satisfaction with prenatal care, preterm birth, having infants small for gestational age, and high rates of cesarean deliveries. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The majority of this research is based on delivery records or surveys like the Pregnancy Risk Assessment Monitoring System (PRAMS), which contain only live birth outcomes and therefore do not reflect early pregnancy loss or miscarriage. Thus, considerably less is known about the association between disability and miscarriage.…”
Section: Introductionmentioning
confidence: 99%